Assessing patients decision‐making capacity in the hospital setting: A literature review. (20th January 2020) - John, Shibu; Rowley, Joanne; Bartlett, Kerry
Abstract: Objective: Decision‐making capacity assessments for hospital settings are challenging as it is dominated by the ethical and legal principles of maintaining autonomy and protection. Health clinicians, especially in rural areas, are challenged with a lack of a standardised processes and pathways for decision‐making capacity assessment. A literature review was conducted to determine what measurement tools clinicians are utilising in the hospital setting for decision‐making capacity assessment and how decisions relating to consent to treatment, independent living and finances are made. Design: Literature review. Method: A search of MEDLINE, EMBASE and PsycINFO databases from January 2006 to April 2019 was conducted for peer‐reviewed articles to determine how decision‐making capacity assessments are conducted and the tools clinicians are utilising in the hospital setting. Results: Five main themes were identified from this review: (a) domains of capacity; (b) capacity assessment; (c) capacity assessment instruments; (d) who performs capacity assessment; and (e) challenges and limitations to capacity assessment in the hospital setting. Currently, there is no gold standard for capacity assessment. Conclusion: This review shows that there is currently a lack of a uniform approach or a singular test to determine capacity. It is proposed that a multidisciplinary approach to decision‐making capacity assessment could be an effective model in the hospital setting, especially in rural health due to limited access to aged care specialists. It is important that clinicians receive ongoing training in decision‐making capacity assessment and further research is recommended in this specialised area of practice.